(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, spiders that do not weave webs are one of the most common species in nature, they are distinguished by their adaptability to various environmental conditions, various ecosystems, they are an integral part of the animal population, and play an important role in the food chain. .role playing is discussed. The unique features of their diversity, reproduction and nutrition contribute to their wide distribution in various types of biogeocenoses. During the study, based on an analysis of the literature, the study of arachnofauna in the regions of Russia and Uzbekistan was analyzed, and the research was carried out on raspberry fields planted in the farms of the Uchkoprik and Kuva regions, by partially changing the generally accepted method (Barber trap). ). In the course of the work, the researcher studied the biological characteristics of representatives of the families Salticidae and Thomisidae. The eyes of these spiders are well developed, they quickly perceive danger and prey, and the front legs have partially changed, which indicates the importance of these legs in hunting.